2021
DOI: 10.3390/toxics9080180
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pesticides in House Dust and Residential Proximity to Farmland in a Rural Region of Taiwan

Abstract: Pesticide drift was reported in many international studies, but rarely studied in Taiwan. We conducted a study in a rural region of Taiwan to examine the associations between pesticides in house dust and nearby agricultural areas using geographic information system (GIS). A questionnaire regarding home characteristics and pesticide use, and indoor and outdoor dust samples were collected from 47 rural homes. Dust samples were analyzed for six pesticides, and agricultural land data for GIS analysis were retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Finally, the poor correlation between VFD and DDM for several pesticides shows that results can be variable depending on the method used. Though, a recent study comparing pesticides in vacuumed outdoor and indoor dust also reported similar correlation ranges (overall moderate) (Simaremare et al, 2021). Correlations between the two matrixes can also be influenced by cleaning habits and other parameters (such as leaving windows open).…”
Section: Pesticides In Vfd and Ddm: How Do They Correlate?mentioning
confidence: 57%
“…Finally, the poor correlation between VFD and DDM for several pesticides shows that results can be variable depending on the method used. Though, a recent study comparing pesticides in vacuumed outdoor and indoor dust also reported similar correlation ranges (overall moderate) (Simaremare et al, 2021). Correlations between the two matrixes can also be influenced by cleaning habits and other parameters (such as leaving windows open).…”
Section: Pesticides In Vfd and Ddm: How Do They Correlate?mentioning
confidence: 57%
“…However, it is unclear whether these differences are due to spray drift and subsequent partitioning to dust, to take home exposures, or brought in via shoes, as it is known that indoor dust is composed of about 35% outdoor soil [ 97 ]. Negative associations between the levels of pesticides in house dust and the distance from the farms have also previously been reported in some studies [ 42 , 43 , 53 , 54 , 59 , 98 ] as well as positive ones between the levels of pesticides in house dust and agricultural acreages around the house [ 99 ], but this trend was not found in other studies [ 55 , 80 , 81 ]. In the present work, this was observed only for two pesticides out of the ten found.…”
Section: Discussionmentioning
confidence: 71%
“…More specifically, chlorpyrifos, terbuthylazine, carbaryl, diazinon, carbendazim, and tebuconazole were frequently quantified (in 59–96% of the samples). In particular, chlorpyrifos, which is associated with neurotoxic and developmental effects [ 4 , 82 ], was the most frequently quantified pesticide in dust, similarly to what has been found in the USA [ 17 , 19 , 38 , 83 ], Pakistan [ 84 ], or Taiwan [ 81 ]. Its widespread occurrence in the two studied areas in environmental media (dust, air, soil, and water [ 64 , 68 , 69 , 70 ]) and human samples [ 64 , 82 ] is related to its common agricultural use, which was previously reported [ 70 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Such hypothesis-driven approaches are the basis for intervention studies designed to identify and mitigate specific indoor sources of target substances. Information about local outdoor sources and occupations helps to identify contaminants from vehicular traffic and nearby industry such as mining and smelting operations [ 23 , 24 , 36 ], and contaminants brought home from the workplace [ 2 ], including take-home exposures to pesticides from agricultural fields [ 37 , 38 ]. Questionnaires that accompany house dust studies also vary depending on whether researchers administer the questionnaire during the home visit, as in the Canadian House Dust Study [ 17 , 22 , 39 ], or if participants complete the questionnaire themselves, as in recent Citizen Science approaches [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%